Efficacy of opioid-free anesthesia in reducing postoperative nausea and vomiting following gynecological laparoscopic surgery: a randomized controlled trial - Yanan Shen; Yanan Shen; Yuanyuan Wu; Yuanyuan Wu; Qianqian Tang; Qianqian Tang; Yilong Wang; Yilong Wang; Wei Ma; Wei Ma; Jianwei Wang; Jianwei Wang (Frontiers in Medicine)
BackgroundPostoperative nausea and vomiting (PONV) are a common complication following gynecological laparoscopic surgery, with opioid use being a significant contributing risk factor. Opioid-free anesthesia (OFA) has emerged as an alternative approach to mitigate opioid-related adverse effects. This study aimed to evaluate the efficacy of OFA in reducing PONV and its impact on postoperative recovery.MethodsThis randomized, double-blind, controlled trial enrolled 92 female patients undergoing elective gynecological laparoscopic surgery. The patients were randomized 1:1 into two groups, whereby the OFA group received anesthesia with esketamine (0.3 mg/kg) and dexmedetomidine (0.6 μg/kg), while the control group received conventional opioid-based anesthesia with sufentanil (0.3 μg/kg). Both groups underwent preoperative transversus abdominis plane (TAP) block with ropivacaine (20 mL per side). Standardized perioperative monitoring and analgesic protocols were maintained. The primary outcome was the incidence of PONV within 48 h postoperatively. Secondary outcomes included the Modified Observer’s Assessment of Alertness/Sedation (MOAA/S) score recovery time, postoperative pain scores, antiemetic and analgesic use, and quality of recovery (QoR-15 scores).ResultsOn postoperative day 1, PONV incidence was significantly lower in the OFA group (15.2%) compared to the control group (34.8%) (P = 0.03), and by postoperative day 2, the difference between the groups was no longer statistically significant (P = 0.475). The OFA group exhibited a longer median extubation time (11.0 min vs. 5.5 min, P < 0.001) and a prolonged MOAA/S recovery time (45.0 min vs. 40.0 min, P = 0.012). Pain scores, postoperative sufentanil consumption, and QoR-15 scores did not differ significantly between groups. No patients in either group required postoperative supplemental analgesics, and three patients in each group received antiemetic treatment solely on the first postoperative day.ConclusionOpioid-free anesthesia incorporating TAP block may reduce early PONV following gynecological laparoscopic surgery while maintaining adequate pain control and overall recovery quality.